PENGARUH LITERASI KEUANGAN SYARIAH TERHADAP RENCANA INVESTASI DI PASAR MODAL SYARIAH PADA MAHASISWA EKONOMI ISLAM DI SURABAYA - Ramadhani, Dini Fitria; Cahyono, Hendry (Jurnal Ekonomika dan Bisnis Islam, 2020)
Islamic capital market as a solution for Indonesian Muslims to manage the funds by investing in accordance with the Sharia. The number of Islamic investors are increasing every year, but its number is still far below the conventional investors. Islamic financial literacy is one of the causes of the lack of education in the society which can be proven by the literacy index of Islami financial, which is 8.93 percent, and 37.73 for the conventional 2019. The Muslim community and the most productive age population make Islamic economics students has a great opportunity in increasing the number of investors. This study aims to examine the effect of Islamic financial literacy on investment plans among the Islamic economics students in Surabaya, which are Universitas Negeri Surabaya, Universitas Airlangga, and Universitas Islam Negeri Sunan Ampel. This research use an associative quantitative approach. The overall results of the study indicate that Islamic financial literacy have a significant effect on investment plans. Based on the result of t test, Islamic financial literacy has an effect on the investment plans. Based on the results of the one-way anova test, there is no difference in the average of these three of universities.